High-frequency jet ventilation improves gas exchange in extremely immature infants with evolving chronic lung disease - Plavka, Richard; Dokoupilová, M; Pazderová, L; Kopecký, P; Sebron, V; Zapadlo, M; Keszler, M (American journal of perinatology, 2006)
Extremely preterm infants often develop chronic lung disease (CLD) characterized by heterogeneous aeration; poorly supported, floppy airways; and air trapping. High-frequency jet ventilation (HFJV) with high end-expiratory pressure (optimal lung volume strategy [OLVS]) may improve airway patency, lead to better gas distribution, improve gas exchange, and facilitate extubation. In a pilot trial, this study sought to explore the effect of HFJV on oxygenation, ventilation, and ease of extubation in preterm infants with evolving CLD and refractory respiratory failure (RRF). From September 2002 to October 2004, 12 episodes of RRF developed in 10 ventilated extremely immature infants with evolving CLD (10 on conventional and two on high-frequency oscillation). Chorioamnionitis was confirmed in all infants, patent ductus arteriosus was ligated in five patients, and UREAPLASMA UREALYTICUM was cultured from trachea in four patients. HFJV with OLVS was initiated when oxygenation index (OI) > 10 or exhaled tidal volume (V TE) >or= 7 mL/kg were required to maintain partial pressure of carbon dioxide, arterial (Pa CO2) < 60 mm Hg. Inspiratory time (0.02/s) and frequency (310 to 420/min) were set initially with adjustment of pressure amplitude to keep Pa CO2 between 45 and 55 mm Hg. Ventilatory stabilization and weaning from mechanical ventilation with extubation to nasal continuous positive airway pressure (CPAP) were the goals of this approach. Gas exchange data were analyzed by Analysis of variance for repeated measures. Ten patients on 11 occasions of RRF were extubated to nasal CPAP successfully in a median of 15.5 days. Nine of 10 patients survived (one died of pentalogy of Cantrell), all required supplemental O2 at 36 weeks. Pa CO2 decreased within 1 hour after the initiation of HFJV, and OI decreased by 24 hours. Both remained significantly lower until successful extubation ( P < 0.02). Compared with conventional ventilation or high-frequency oscillatory ventilation, HFJV used with OLVS appears to improve gas exchange and may facilitate weaning from mechanical ventilation (MV) in extremely immature infants with evolving CLD. These encouraging pilot data need to be confirmed in a larger clinical trial.
Keywords: vysokofrekvenční proudová ventilace; novorozenec; Infant, Newborn; High-Frequency Jet Ventilation; Pulmonary Ventilation; klinické křížové studie; Humans; Disease Progression; Oxygen Consumption; Chronic Disease; novorozenec s extrémně nízkou porodní hmotností; lidé; plicní nemoci; Infant, Premature, Diseases; pilotní projekty; Pilot Projects; plicní ventilace; nemoci nedonošenců; Lung Diseases; chronická nemoc; spotřeba kyslíku; Infant, Extremely Low Birth Weight; progrese nemoci; Cross-Over Studies